Faktor – Faktor Pertengkaran antara Suami dan Istri di dalam Rumah Tangga Serta Pemicunya - Christine Purnamasari Andu (Communications, 2021)
The aims of this study is to know (1) the quarrel factors between husband and wife in a household and (2) the caused of its quarrel. Data used for this research are primary and secondary data. Primary data or main datais taken from the informants itself, and secondary data or additional data are collected from another sources such as books, journals, websites, and other valid source to support this study completion. Total informants are twenty, consist of ten wives, and ten husbands, while some of those twenty were already widow and widower. All primary datas were collected by interviewed and secondary datas were supported by books, journals, and websites. Researcher used two theories namely Expectancy Violations Theory and Behaviorism Theory. At the beginning of this interviewed with the informants, researcher has already gavetwelve indicatorsso it couldmake the easier to choose their choices based on their real situations and then explain it. Study showed that (1) the quarrel factors between husband and wife from the husband point of viewed were : housedhold tasks and bad habbits (42%), phone/social media and economy (33%), and in-laws/other family (25%). From the wife side were : disloyalty (42%), economy and in-laws/other family (33%), household tasks, bad habits and commitment (25%).